OUTCOME OF ’˜BASIC LIFE SUPPORT TRAINING’ IN A BUSY DISTRICT GENERAL HOSPITAL - Anwer, Ambreen; Malik, Wasim Ahmad; Khan, Ammanat (Journal of Ayub Medical College Abbottabad, 2010)
Background: In view of the recently increasing terrorist attacks, hospitals have to devote an increased attention to Disaster Management. An effective way to do this is by preparing disaster plans and training ’˜hospital staff response team’. Most of the District General Hospitals (DGH) act as first point of contact in emergency. Our practical experience revealed that if the staff is not trained well for an organised and structured response, rather than help they can become an unnecessary hindrance. In the current scenario we felt a dire need to train as many staff members as possible in Basic life support (BLS). The objective was to train as well as assess the feasibility of training these skills to a mixed ability group of health professionals in a busy DGH. Methods: Twelve training sessions of 1 hour/week were planned. Twenty-nine candidates with mixed ability health workers (5 Medical Officers, 10 Nurses, 9 Nursing Assistants, 2 LHV, 3 Ayahs) were enrolled. Each session was planned as initial 20 min lecture presentation followed by practical demonstration and 30 minutes hands on training with final 10 minutes for feedback. Final Assessment was performed by an independent assessor. Post training feedback was acquired through an open ended questionnaire. Results: The outcome of training showed 24 participants fully trained and successful in first attempt. There were total 5 drop-outs during the training program. Conclusion: It is feasible to run this program regularly in a District General Hospital with few adjustments in the administrative arrangements. Results of training can be much more improved if institutional commitment is linked to such training pursuits and ’˜protected teaching time’ is ensured. Keywords: Basic Life Support, Life Support Courses, Emergency Medicine, Disaster management